2014
DOI: 10.1371/journal.ppat.1004162
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale RNAi Reveals the Requirement of Nuclear Envelope Breakdown for Nuclear Import of Human Papillomaviruses

Abstract: A two-step, high-throughput RNAi silencing screen was used to identify host cell factors required during human papillomavirus type 16 (HPV16) infection. Analysis of validated hits implicated a cluster of mitotic genes and revealed a previously undetermined mechanism for import of the viral DNA (vDNA) into the nucleus. In interphase cells, viruses were endocytosed, routed to the perinuclear area, and uncoated, but the vDNA failed to be imported into the nucleus. Upon nuclear envelope perforation in interphase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
202
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 135 publications
(222 citation statements)
references
References 84 publications
17
202
1
2
Order By: Relevance
“…Our observations are somewhat contradictory to recently published findings purporting that arresting cells in a monoastral phenotype does not block HPV16 infection (34). However, a careful analysis reveals that Eg5 inhibition is leaky and that a minority of cells complete an additional cell cycle rather than being arrested in mitosis.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our observations are somewhat contradictory to recently published findings purporting that arresting cells in a monoastral phenotype does not block HPV16 infection (34). However, a careful analysis reveals that Eg5 inhibition is leaky and that a minority of cells complete an additional cell cycle rather than being arrested in mitosis.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our observations, a previous study reported that inhibition of Eg5 has no effect on pseudoviral infectivity in both HeLa and HaCaT cells (34). In line with that study, we also observed no significant inhibition of infection in the presence of Eg5i (Fig.…”
Section: Incoming Viral Genome Is Protected From Nuclease Digestion Dsupporting
confidence: 62%
See 3 more Smart Citations